Persepsi Mahasiswa Tahap Profesi Kedokteran terhadap Interprofessional Education - Resti Rahmadika Akbar (Universitas Baiturrahmah, 2021)
Introduction: The introduction of the concept of collaborative health education that has been launched by WHO aims to improve health services. Collaborative media initiated by WHO is Interprofessional Education (IPE). Professional stage students are expected to cooperate with other health professions. A positive perception of IPE acceptance is expected to be taken into consideration by institutions for the development of the IPE concept at the Faculty of Medicine at Universitas Baiturrahmah. Aims: The purpose of this study was to determine perceptions of medical professional stage students towards IPE. Method: This type of research is quantitative with a descriptive analysis design with a cross-sectional approach. The research sample was used in consecutive sampling. Retrieval data with a modified IEPS (Interprofessional Education Perception Scale) questionnaire. Results: The results showed the reliability of the IEPS questionnaire 0.890. The modified IEPS questionnaire has 12 statements. The majority of the perception of medical professional stage students is positive 92.3%. The subcategory of competence and autonomy are good at 89.7%, the need to work together is good at 97.4% and perceptions about collaboration are good at 89.7%. Conclusion: The majority of students' perceptions of interprofessional education are good and need strategies and communication from educational institutions and teaching hospitals in its implementation.